Cross-stacked carbon nanotube film as an additional built-in current collector and adsorption layer for high-performance lithium sulfur batteries. (18th January 2016) - Sun, Li; Kong, Weibang; Li, Mengya; Wu, Hengcai; Jiang, Kaili; Li, Qunqing; Zhang, Yihe; Wang, Jiaping; Fan, Shoushan
Abstract: Cross-stacked carbon nanotube (CNT) film is proposed as an additional built-in current collector and adsorption layer in sulfur cathodes for advanced lithium sulfur (Li-S) batteries. On one hand, the CNT film with high conductivity, microstructural rough surface, high flexibility and mechanical durability retains stable and direct electronic contact with the sulfur cathode materials, therefore decreasing internal resistivity and suppressing polarization of the cathode. On the other hand, the highly porous structure and the high surface area of the CNT film provide abundant adsorption points to support and confine sulfur cathode materials, alleviate their aggregation and promote high sulfur utilization. Moreover, the lightweight and compact structure of the CNT film adds no extra weight or volume to the sulfur cathode, benefitting the improvement of energy densities. Based on these characteristics, the sulfur cathode with a 100-layer cross-stacked CNT film presents excellent rate performances with capacities of 986, 922 and 874 mAh g −1 at cycling rates of 0.2C, 0.5C and 1C for sulfur loading of 60 wt%, corresponding to an improvement of 52%, 109% and 146% compared to that without a CNT film. Promising cycling performances are also demonstrated, offering great potential for scaled-up production of sulfur cathodes for Li-S batteries.